Mechanisms of epigenetic inheritance of variable traits through the germline. Issue 6 (June 2020) - Casas, Eduard; Vavouri, Tanya
Abstract : During the past half century, evidence for inheritance of variable traits has accumulated from experiments in plants and animals and epidemiological studies in humans. Here, we summarize some of the reported cases of epigenetic inheritance and the proposed mechanisms involved in the transmission of non-genetic information between generations in plants, nematodes, flies and mammals. It has long been accepted that information is epigenetically inherited in plants. Although many questions regarding the underlying mechanisms remain to be answered, it is now evident that epigenetic mechanisms are also responsible for the transmission of phenotypes in animals. We highlight similarities and differences between models and species.